Kultura w sieci, czyli dlaczego papierowe czasopisma kulturalne znikają i nie odradzają się w Internecie = Culture on the web: why paper-based cultural magazines are disappearing and are not being revived on the Internet - Darska, Bernadetta (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article is an attempt to examine trends in cultural magazines in Poland after1989. Special emphasis is placed on the 21st century, when, after a period of enthusiasm, one can speak of there being a crisis, together with problems affecting a growing group of titles. An important point of reference is the internet, which is presented in the light of reflections and questions concerning the use of the possibilities it offers.
Keywords: czasopisma kulturalne; czasopisma polskie; czasopisma papierowe; internet; Media społecznościowe; cultural magazines; Polish magazines; paper magazines; social media